Effects of Herbicide Application Timing and Tillage System on Tobacco Plant (Nicotiana tabacum L.) - Vanindyantara Nugra Pratama (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2016)
This research aims to study the result of proper glyphosate and paraquat application and tillage system as weed controller and to get the proper herbicide application timing and soil tillage system for increased growth and yield of tobacco. The research was conducted in Pakel Village, Sumberpucung District, Malang Regency in July-October 2014. Method used in the research was Split-Plot design with 2 levels of tillage system as main plot and 6 levels of application herbicide timing as sub-plot with 3 replications. Glyphosate application before planting increased growth factor of tobacco i.e. number of leaves, plant height, and leaf area. Glyphosate application before tillage and planting increased yield factor of tobacco i.e. fresh weight of roots and stems, fresh weight of leaves, dry weight of chopped tobacco, and nicotine content.